2011
DOI: 10.1099/mic.0.043794-0
|View full text |Cite
|
Sign up to set email alerts
|

Clp-dependent proteolysis of the LexA N-terminal domain in Staphylococcus aureus

Abstract: The SOS response is governed by the transcriptional regulator LexA and is elicited in many bacterial species in response to DNA damaging conditions. Induction of the SOS response is mediated by autocleavage of the LexA repressor resulting in a C-terminal dimerization domain (CTD) and an N-terminal DNA-binding domain (NTD) known to retain some DNA-binding activity. The proteases responsible for degrading the LexA domains have been identified in Escherichia coli as ClpXP and Lon. Here, we show that in the human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 43 publications
(59 reference statements)
3
43
0
Order By: Relevance
“…We also identified the clpP gene encoding the proteolytic subunit of the ClpXP two-component protease to be more susceptible to ciprofloxacin, corroborating a study in P. aeruginosa (Fernández et al, 2012). A possible link between clpP and ciprofloxacin susceptibility is that clpP has been shown to interfere with activation of the SOS DNA-damage response (Cohn et al, 2011). Additionally, inactivation of several hypothetical genes ( SAUSA300_1789 and SAUSA300_2311 ) also conferred a fourfold or greater sensitization to ciprofloxacin relative to the WT strain.…”
Section: Resultsmentioning
confidence: 99%
“…We also identified the clpP gene encoding the proteolytic subunit of the ClpXP two-component protease to be more susceptible to ciprofloxacin, corroborating a study in P. aeruginosa (Fernández et al, 2012). A possible link between clpP and ciprofloxacin susceptibility is that clpP has been shown to interfere with activation of the SOS DNA-damage response (Cohn et al, 2011). Additionally, inactivation of several hypothetical genes ( SAUSA300_1789 and SAUSA300_2311 ) also conferred a fourfold or greater sensitization to ciprofloxacin relative to the WT strain.…”
Section: Resultsmentioning
confidence: 99%
“…In S. aureus, very few substrates of ClpC/XP have been identified, although ClpCP has been implicated in degradation of antitoxins (10). Cohn et al (11) showed that ClpXP, and to a lesser extent ClpCP, are involved in regulating the SOS response and thus affect expression of a subset of SOS regulon genes by degrading the LexA N-terminal domain after autocleavage of LexA. E618A) mutation, referred to as clpC trap , was constructed via overlapping PCR in two steps, using the primers listed in Table 2.…”
mentioning
confidence: 99%
“…In S. aureus, the ClpPX as well as the ClpPC proteases contribute to degradation of LexA autocleavage products (Cohn et al, 2011). Therefore, the low level of persisters observed in clpP mutant cells may be attributed to a decrease in overall stress response, and the differences among antibiotics may be explained through the antibiotics, specific target and degree of stressors (Kim et al, 2011).…”
Section: Effect Of Clpp Deletion On Persister Cell Number After Antibmentioning
confidence: 99%